'BOMBILE' – Newest enemy to our sight? – A case series. (January 2022) - Sharda, Pranidhi; Panwar, Praveen
As possession of a mobile phone becomes ubiquitous in the general population, its hazards, especially for vision, should be better known and understood. Although blast injuries are common in war, gas cooking and with firecrackers, mobile phone blasts, popularly known as BOMBILE (Blast of Mobile Battery in the Living Eye), are becoming more and more frequent. We present three cases phone battery explosion diagnosed with ocular surface burn. Although none had severe injuries and vision was salvageable and no visual or cosmetic impairment resulted, this may not always be so. Public education, producer liability, and better technological solutions are urgently required to lessen the risks.